A Survey on Occupational Injuries in Works on Trees in Italy. (10th June 2016) - Proto, A.R.; Mazzocchi, F.; Cossio, F.; Bortolini, L.; Pascuzzi, S.; Caruso, L.; Diano, M.; Zimbalatti, G.
Abstract: The aim of this work is to know how many injuries occur during climbing and pruning to arborists and other operators who work on trees, the type of accidents and why they happen. This study was carried out during the period from 2002 to 2012 using INFORMO, the database of INAIL (National Organization for the Labour Insurance) that contains a list of serious and fatal injuries occurred to workers and counted by its Prevention Service. From this list only accidents related to operators who was working on trees, at least 2 meters above a stable ground without using elevating work platform, have been extracted. In these workplaces, operators should work safely using tree-climbing techniques with ropes and harness. The scope of the study was to understand the common triggers of injuries, if there are technical problems that can be solved, or other problems that can be addressed to decrease the number of accidents and their severity.